Use of Common Langurs (Semnopithecus spp.) as Guard Animals in India: Some Legal and Practical Aspects - Bist, S. S. (Indian Forester, 2017)
The Human-Macaque Conflict has become a serious issue in many parts of India. The State Forest Departments are hardpressed to find suitable and effective measures for mitigating this conflict. Use of common langurs (Semnopithecus spp.) as guard animals for scaring away troublesome macaques has evolved entirely through people’s initiative to solve their own problems. Usefulness of the guard langurs is borne out by their large-scale deployment in the country. However, this practice has given rise to illegal capture and trade of common langurs. The animal right activists have also raised concerns about the welfare of the guard langurs. The advisory issued by the Wildlife Crime Control Bureau in October 2012 prohibiting the use of common langurs as guard animals has put the conflict-managers at a great disadvantage. The advisory is being violated even by the authorities at the highest levels. It has neither helped in ensuring welfare of the captive langurs nor in better compliance with the existing laws. A more pragmatic approach will be to regulate use of the guard langurs rather than ban it. This paper proposes a strategy for managing the Human-Macaque Conflict using the guard langurs in conformity with the provisions of the Wildlife (Protection) Act, 1972 and the Prevention of Cruelty to Animals Act, 1960 without compromising with the conservation status of the species in the wild.